Microstructure, mechanical properties and corrosion behavior of friction stir back extruded AZ91-bioactive glass composite after post processing aging - Pourya Motavallian; Sayed Mahmood Rabiee; Hamed Jamshidi Aval (Results in Engineering)
A research study was conducted to examine the effects of thermal treatment and bioactive glass (BG) particles on the microstructure, mechanical properties, and corrosion behavior of a composite based on an AZ91 alloy matrix. This composite underwent friction stir back extrusion. The findings revealed that in solution-treated samples, the β-Mg₁₇Al₁₂ phase dissolved into the matrix and subsequently re-precipitated along grain boundaries during the aging process. Significant improvements in mechanical properties and corrosion resistance were observed following an aging treatment at 200 °C for 12 h. Prior to aging, the composite exhibited an optimal combination of ultimate tensile strength (365.8 MPa), yield strength (276.4 MPa), elongation (7.95 %), and hardness (77.58 HV) after undergoing friction stir back extrusion—surpassing the properties of the solution-treated samples. The corrosion resistance was enhanced due to the uniform dispersion of the β-Mg₁₇Al₁₂ phase in peak-aged samples. In a simulated body fluid solution, the minimum corrosion rate (1.86 mm/year) was recorded for the AZ91 composite containing 3 vol. % BG after 12 h of aging. This represents a reduction of over 40 % compared to the corrosion rate (2.79 mm/year) of AZ91 samples without BG reinforcement.